Selected Elements of Governance Under Conditions of Conflicts and Crises, And Sustainable Development of Enterprises and Corporations - Jerzy WACHOL (Communications of International Proceedings, 2023)
The study presents selected elements of governance in the face of armed conflict, economic and social crises, taking into account sustainable development in the face of a changing environment and climate. Socio-economic data and trends of changes in the global economy were presented, where the 2020 crisis was followed by economic upturn in 2021 and 2022. However, further risks of economic and financial crisis in 2024 are projected, due to continued armed conflicts, sanctions, indebtedness of countries and organizations, further possible epidemics, generally more expensive energy resources, economic and political differences, as well as population migrations. The problems of today's global economy and sustainable development under conditions of pandemics, war and threats of economic crisis are all presented. The study stresses the significance of big corporations and climatic change. The paper also presents the importance of selected elements of governance according to own survey research. Nowadays, elements such as financial factors, social, human resources, marketing, technology, IT, various governance methods including time management, lean management, outsourcing, etc. play an important role in enterprises. Ecological factors also play an all-important role within the framework of a changing climate, environmental pollution and dwindling natural resources. As the survey research shows, respondents also value their health and work, and are unlikely to fear war or pandemics. The study also includes a comparison and discussion of economic and social data and CO2 emission data in selected countries across the world from 2020 to 2023. Based on the collected statistical data, study and own survey research, conclusions were drawn.
Keywords: elements of governance; economic crisis; sustainable development; corporations; globalization